Development of quantitative multiplex real-time RT-PCR assays for detection of 13 conventional and newly discovered viruses associated with lower respiratory tract infections in children in South Africa - Venter, Marietjie (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.